Focusing on heel strike improves toe clearance in people with Parkinson's disease: an observational pilot study. Issue 4 (December 2017) - Ginis, Pieter; Pirani, Rudi; Basaia, Silvia; Ferrari, Alberto; Chiari, Lorenzo; Heremans, Elke; Canning, Colleen G.; Nieuwboer, Alice
Abstract: Objectives: To investigate differences in toe clearance between people with PD and age-matched healthy elderly (HE) during comfortable walking and to study the effects of dual-tasking and the use of an attentional strategy emphasizing heel strike on toe clearance. Design: Observational cross-sectional study. Setting: Camera-based 3D gait laboratory. Participants: Ten persons with PD (Hoehn and Yahr I to III) having mild gait disturbances and 10 HE. Interventions: Participants walked for two minutes under three conditions at comfortable pace: single-task walking, attending to heel strike during single-task walking, and dual-task walking. Main outcome measures: Minimal and maximal toe clearance; foot strike angle with the ground. Results: People with PD had less maximal toe clearance in the end of the swing phase and a smaller foot strike angle than HE during all three walking conditions. Impairments significantly diminished during heel strike focused walking improving performance to equal the HE. Heel strike focused walking resulted in an increased minimal toe clearance and a longer duration of end swing phase when compared to walking with and without a dual-task. The attentional strategy to focus on heel strike improved the stride length when compared to dual-task walking. Surprisingly, minimal toe clearance did not differ between PD and HE in any of the conditions and there were no dual-task effects on toe clearance. Conclusion: These findings provide evidence favoring the potential incorporation of an attentional strategy focusing on the heel strike in PD gait rehabilitation.